An alternative asymmetric figure-of-eight single-layer suture technique for bowel anastomosis in an in vitro porcine model - Liu, Chen; Wang, Yewen; Zhao, Ai-rong; Hu, Feng-ai; Fan, Qizhong; Han, Guoxiu; Ding, Guojian; Fu, Tingliang; Geng, Lei; Yin, Hongshan (Frontiers in Surgery, 2022)
Anastomotic techniques are of vital importance in restoring gastrointestinal continuity after resection. An alternative asymmetric figure-of-eight single-layer suture anastomotic technique was introduced and its effects was evaluated in an in vitro porcine model. Twelve 15-cm grossly healthy small intestine segments from a porcine cadaver were harvested and randomly divided into asymmetric figure-of-eight single-layer suture (figure-of-eight suture) and single-layer interrupted suture technique (interrupted suture）groups (n = 6 in each group). The anastomosed bowel were infused with methylene blue solution to test anastomotic leakage. Anastomosis construction time, leakage, and suture material cost were recorded and analyzed statistically using Fisher’s exact test and Student’s t-test. One anastomotic leakage occurred (16.67%) in the figure-of-eight suture group, and two (33.33%) in the interrupted suture group (p＞ 0.9999). The anastomosis construction time was relatively short in the figure-of-eight suture group, but the difference did not reach a statistically significant level between the two groups. The mean number of suture knots and the cost of suture material in the figure-of-eight suture group were significantly decreased in comparison to interrupted suture group (15.67 ± 3.30 vs 22.17 ± 2.03, 167.11 ± 35.20 vs 236.45 ± 21.70 CNY, p < 0.01, respectively). Our results suggested that the alternative asymmetric figure-of-eight suture technique was safe and economic for intestinal anastomosis. An in vivo experiment is required to elucidate the effects of this suture technique on the physiological anastomotic healing process.